2017
DOI: 10.3390/inorganics5040087
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Rh-Catalyzed Transformation of Fatty Acids to Linear Alpha olefins

Abstract: Linear alpha olefins (LAOs) are key commodity chemicals and petrochemical intermediates that are currently produced from fossil resources. Fatty acids are the obvious renewable starting material for LAOs, which can be obtained via transition-metal-catalyzed decarbonylative dehydration. However, even the best catalysts that have been obtained to date, which are based on palladium, are not active and stable enough for industrial use. To provide insight for design of better catalysts, we here present the first co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Initially, reaction (1) was achieved on fatty acid with the aid of an anhydride additive (like acetic anhydride) and Pdor Rh-based complexes with good LAO selectivity: 14,16 R-CH2-CH2-COOH + (CH3CO)2O  R-CH=CH2 + CO + 2CH3COOH (3) More recently, it was shown that (3) can be performed effectively with metallic Pt or Pd on C preserving the high selectivity toward LAO. 17,18 The mechanism of such dehydration-decarbonylation reactions is discussed in detail by Eliasson et al 19 The research on LAO formation from fatty acids involved also the adoption of pre-formed Pdcomplexes which reduce the amount of triphenylphosphine (TPP) used as reaction solvent, 20 and a study on the effect of different phosphine ligand structures on the selectivity toward LAO or the conversion of fatty acids to LO/LAO with Pd complexes. [21][22][23] The research also moved toward the study of more economical and wide available catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, reaction (1) was achieved on fatty acid with the aid of an anhydride additive (like acetic anhydride) and Pdor Rh-based complexes with good LAO selectivity: 14,16 R-CH2-CH2-COOH + (CH3CO)2O  R-CH=CH2 + CO + 2CH3COOH (3) More recently, it was shown that (3) can be performed effectively with metallic Pt or Pd on C preserving the high selectivity toward LAO. 17,18 The mechanism of such dehydration-decarbonylation reactions is discussed in detail by Eliasson et al 19 The research on LAO formation from fatty acids involved also the adoption of pre-formed Pdcomplexes which reduce the amount of triphenylphosphine (TPP) used as reaction solvent, 20 and a study on the effect of different phosphine ligand structures on the selectivity toward LAO or the conversion of fatty acids to LO/LAO with Pd complexes. [21][22][23] The research also moved toward the study of more economical and wide available catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Once the anhydride is formed there is the interaction with the metal catalyst, with oxidative addition of the metal, the decarbonylation step and the alkene formation and release. 19 In literature the complex bis(triphenylphosphine)nickel(II) dichloride (i.e. (Ph3P)2NiCl2) was reported as an effective decarbonylation reagent of certain cycloaliphatic anhydrides.…”
Section: Introductionmentioning
confidence: 99%
“…Only during the work with this thesis, have the first computational studies of the reaction arrived. 66,74,[81][82][83][84] This lack of mechanistic information has stifled the understanding of different factors of the reaction and rational design of better catalysts, and was partly the motivation for synthesizing the molecular well-defined precatalyst A1, Pd(cinnamyl)Cl(DPEphos). 85 While previous catalysts for decarbonylative dehydration have been formed in situ, this catalytic system was able to transform fatty acids to α-olefin at relatively mild conditions (110°C) and, importantly, without excess of phosphine.…”
Section: Introductionmentioning
confidence: 99%
“…Eliasson, Chatterjee, Occhipinti and Jensen published a comprehensive computational study on the mechanism of the Rh-mediated decarbonylative dehydration of fatty acids to provide linear terminal alkenes (LAO) and carboxylic acid, with anhydride as the co-reagent [29]. Furthermore, the authors investigated the mechanism of Pd-systems for the same reaction in order to find similarities and differences between both catalyst types, to draw conclusions regarding the relative rates and to provide avenues for catalyst optimization.…”
mentioning
confidence: 99%
“…Furthermore, the authors investigated the mechanism of Pd-systems for the same reaction in order to find similarities and differences between both catalyst types, to draw conclusions regarding the relative rates and to provide avenues for catalyst optimization. Linear terminal alkenes or linear alpha olefins are key commodity chemicals and petrochemical intermediates that are e.g., used in the large-scale technical synthesis of oxo alcohols to give detergents and plasticizers [29], using e.g., the hydroformylation reaction [2].…”
mentioning
confidence: 99%